-10(s+5)=-53

Simple and best practice solution for -10(s+5)=-53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(s+5)=-53 equation:


Simplifying
-10(s + 5) = -53

Reorder the terms:
-10(5 + s) = -53
(5 * -10 + s * -10) = -53
(-50 + -10s) = -53

Solving
-50 + -10s = -53

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '50' to each side of the equation.
-50 + 50 + -10s = -53 + 50

Combine like terms: -50 + 50 = 0
0 + -10s = -53 + 50
-10s = -53 + 50

Combine like terms: -53 + 50 = -3
-10s = -3

Divide each side by '-10'.
s = 0.3

Simplifying
s = 0.3

See similar equations:

| -4n-8=4(-3n+2) | | 9e^1=16 | | 25x-(8)=22x+10 | | 4x(5x+1)=5x+1 | | 2x=x-(8) | | 8r-7=2r+35 | | 16x+8x=10 | | 18y+-x=-25 | | 3x-4=1x | | 1600x+800y=1000 | | y=1.38(3.5)-0.52 | | Y+4=3(x-2) | | -x+18y=-25 | | 7-2*2+(8-6)= | | 5x+14.5=0 | | -9(x-(9))=3(x+47) | | 17=k-2 | | -12(x-(9))=3(x+16) | | -5(z+1)=-2z+10 | | 3Xsquared+5X=0 | | 1.4=n-2 | | -7x-(2.8)=6x-(13.2) | | 9s+9=30 | | 7x-(2.7)=-6x-(7.9) | | 8S-23=-14+5S | | 34-23= | | 180=3x+75 | | (x-2)2+(y+7)2=169 | | 7p-12=-36+4p | | 12k-3(k+5)=-8 | | 5y-y^2=11 | | y=5(2x-1)(x-4) |

Equations solver categories